3D reconstruction to create pervasive augmented reality experiences - Neves, Pedro Miguel Oliveira (2021)
Nowadays, additional information can be required to aid with certain tasks as well as to enhance educational and entertainment experiences. A possible solution to support these activities is the use of Augmented Reality (AR), allowing an easier access and a better perception of additional layers of content superimposed onto reality. In this context, Pervasive AR experiences can be used to enrich the real world with virtual content that is visualized continuously as the user moves through the space. However, the creation of such experiences depends on authoring tools that overcome the existing difficulties and facilitate this task. These must be accessible for inexperienced users while also providing experts the full potential of the technology. In this dissertation, two applications were developed: desktop and mobile, both capable of being used for the creation, configuration and visualization of pervasive AR experiences. The system developed makes use of a scan of a physical environment to provide a digital reconstructed representation of that space to the desktop platform and to enable the positional tracking in the mobile platform. While the desktop application presents the user with a non-immersive Virtual Reality (VR) setting and the mobile application provides continuous AR in the physical environment, both scenarios can be used to place virtual content on and ultimately configure an AR experience. The authoring capabilities of both platforms were compared by conducting a user study focused on evaluating their usability. As a result, the positive feedback of the participants shows that these platforms appear to be a valid solution to pursue the goal of having pervasive experiences in large environments, which users can explore, interact with and learn from.